Análisis de los Requerimientos de una Solución Informática para la Digitalización de Documentos en el departamento de Investigación y Desarrollo de la Universidad Técnica de Babahoyo - Moran León, Miguel Daniel (2017)
We are in the century of information and becoming full of knowledge and always be updated with technology that provides us with efficient and agile services that helps any company, information is the most important asset of companies or institutions, which must be supported and protected in which we find it within each department and in each of the documents we produce and receive, sometimes misplaced documents and it is very harassing to look in each (folder, folders, filing cabinets) a document. The research and development institute of the Technical University of Babahoyo is a scientific research center that contributes to the formation of human talent in the community through the generation of research projects according to the requirements of institutional, local development , provincial, regional and national level, whose main objective is to promote, classify, strengthen and elaborate the Scientific and Technological Research in the different academic units that make up the University and other external actors, which will strengthen our potential in science and technology through projects research aimed at improving the quality of life of the population. For all research projects must comply with the appropriate regulations for the necessary control of compliance with scientific and technological research projects and programs. Knowing the basic techniques and concepts for the digitization of printed documents is, therefore, a prerequisite for all information professionals, this is important to understand what a digitized document means and when to call it that a document.